Spermatozoa telomeres determine telomere length in early embryos and offspring. Issue 1 (January 2016) - de Frutos, C; López-Cardona, A P; Fonseca Balvís, N; Laguna-Barraza, R; Rizos, D; Gutierrez-Adán, A; Bermejo-Álvarez, P
Abstract : Offspring telomere length (TL) has been correlated with paternal TL, but the mechanism for this parent of origin-specific inheritance remains unclear. The objective of this study has been to determine the role of spermatozoa TL in embryonic telomere lengthening by using two mouse models showing dimorphism in their spermatozoa TL: Mus musculus vs Mus spretus and old vs young Mus musculus . Mus spretu s spermatozoa displayed a shorter TL than Mus musculus . Hybrid offspring exhibited lower TL compared with Mus musculus starting at the two-cell stage, before the onset of telomerase expression. To analyze the role of spermatozoa telomeres in early telomere lengthening, we compared the TL in oocytes, zygotes, two-cell embryos and blastocysts produced by parthenogenesis or by fertilization with Mus musculus or Mus spretus spermatozoa. TL was significantly higher in spermatozoa compared with oocytes, and it increased significantly from the oocyte to the zygote stage in those embryos fertilized with Mus musculus spermatozoa, but not in those fertilized with Mus spretus spermatozoa or produced by parthenogenesis. A further increase was noted from the zygote to the two-cell stage in fertilized Mus musculus embryos, whereas hybrid embryos maintained the oocyte TL. Spermatozoa TL shortened with age in Mus musculus and the offspring from young males showed a significantly higher TL compared with that fathered by old males. These significant differences were already noticeable at the two-cell stage. These results suggest that spermatozoa telomeres act as a guide for telomerase-independent telomere lengthening resulting in differences in TL that persist after birth. Free Spanish abstract : A Spanish translation of this abstract is freely available athttp://www.reproduction-online.org/content/151/1/1/suppl/DC1 .